Pedagogical renovation and teachers identities: a comparative study of public examination files and Francoist purge files of primary headteachers of the Second Spanish Republic (1932-1943) - Menguiano Rodríguez, Carlos (Historia y Memoria de la Educación, 2020)
This paper evaluates the possibilities offered by a comparative study between two sources unrelated until now: the personal files from professional selection processes produced during the Second Spanish Republic and the files produced in the Francoist purge process which started at the beginning of the Spanish Civil War. We take a privileged segment of the teaching staff as a sample: the teachers who achieved headteacher positions for the new graded schools in the public exams held in 1932 during the Second Spanish Republic. In order to contextualize the relevance of this contingent of teachers, we first offer a quantitative analysis, showing the impact of the purging process on them. Next, we present the approach from which we perform the qualitative analysis, which is based on the interpretation of the files as “institutional life-archives” and we try to characterise this life-archive practice in both processes, keeping in mind that, although different in modality and purpose, both are valuable sources for studying the professional identities of those who elaborated the files. Finally, we propose three models —confirmation, re-adaptation and dissolution— for performinga qualitative analysis, which make it possible to assess the production and fluctuation of teacher’s identities among these files. These models demonstrate the utility of a comparative analysis of these sources, which can serve to study the configuration of teachers’ professional and pedagogical identities as well as their relationship with the new pedagogical theories and pedagogical tradition in a key time of Spanish history of education. It is our hope that this study will lead to new lines of research in order to analyse the continuities and ruptures of pedagogical discourses and practices between different periods.